Appropriation and political expression in urban public spaces | Apropriação e expressão política nos espaços públicos urbanos - Abrahão, Sergio Luis (Revista Brasileira de Estudos Urbanos e Regionais, 2016)
There are many, diverse issues that determine the relationship between citizens and their public urban spaces and, consequently, the significance that these spaces acquire for society as a whole. In totalitarian regimes however, the use of streets and parks as places of protest and resistance against sequestered freedom is not permitted. However, in democratic regimes, the reflections and discourse of architects, urbanists, researchers and policy makers regarding the manner in which public urban space is (or should be) appropriated by the population, has revealed a systematic reinterpretation of these spaces. Indeed, ever since the last decades of the past century, it has become recurrent to associate these physical spaces with the space of political realization. The intention of the present article is to bring the meaning of this association into debate, above all due to the insurgencies from certain segments of our population, which have taken place over recent years, manifestly in the streets, parks and avenues of our cities.